Oil Price Volatility and Economic Growth: Evidence from the Middle East - Almasria, Nashat Ali; Aldboush, Hassan Hamad; Al-Kasasbeh, Omar; Lutfi, Abdalwali; Alhajahmad, Fadya Burhan; Barrak, Thamir Al; Alsheikh, Ghaith (International Journal of Energy Economics and Policy, 2024)
This paper seeks to study the effect of oil price volatility on economic growth in Middle East countries (Jordan, United Arab Emirates, Saudi Arabia, Kuwait, Qatar, and Turkey). The study's goals were achieved by utilising a range of econometric methodologies. For instance, the IPS and LLC procedures are used to study unit root qualities, while Westerlund and Edgerton's (2008) test is used to study cointegration. The findings demonstrate a long-term correlation between Oil price volatility, inflation, investment, and economic growth. The study concludes with more detailed findings regarding how oil prices affect gross domestic product growth. As such, policymakers can use it to support their decision-making.